Efektivitas Air Rebusan Daun Binahong Dengan Air Rebusan Daun Sirih Terhadap Penyembuhan Ruptur Perineum Pada Ibu Bersalin Di Puskesmas : The Effectiveness of Water Decoction of Binahong Leaves with Water of Betel Leaf Decoction for Healing Perineal Rupture in Mothers Giving Birth at Banjarsari Community Health Center - Amini, Risa Warisatul Zahro; Elfira Sri Futriani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Perineal rupture is a birth canal tear that often occurs in the normal delivery process and is a health problem that must be treated immediately because it can cause infection so treatment needs to be carried out. The data from the Banjarsari Health Center report in 2021 showed that there were 35 cases of perineal rupture (72,91%) from 48 postpartum mothers. The purpose of the research is to find out the effectiveness of boiled water from binahong leaves with boiled water from betel leaves for healing perineal rupture in women giving birth at the Banjarsari Health Center Lebak Regency in 2022. Methods: The research method uses quasi-experiments with a posttest-only design with non-equivalent groups. The sample of this study was a spontaneous postpartum mother who experienced a perineal rupture of 30 people with a sampling technique using simple random sampling. Instruments use questionnaires. The Bivariate analysis uses the paired t-test and independent t-test. Results: The average healing time of perineal rupture given boiled water of binahong leaves is 5,87 (5 to 6 days) while that given boiled water of betel leaves is 7,93 (7 to 9 days). The results of statistical tests show that there is the effectiveness of binahong leaf boiled water with betel leaf boiled water against healing perineal rupture in maternity mothers at the Banjarsari Health Center Lebak Regency in 2022 (p = 0,006). Discussion: Giving boiled water to binahong leaves is faster and more effective in curing perineal rupture compared to giving betel leaf boiled water. It is hoped that postpartum mothers can use non-pharmacological methods using herbal complementary therapy for the treatment of perineal rupture namely by using binahong leaf boiled water or using betel leaf boiled water.